Commuter´s exposure to short-lived climate pollutants in maritime transport - Oliveira, Marcus Vinicius Batista (2020)
The city of Rio de Janeiro (Brazil) hosts a unique maritime mass transit system, operating commute ferries at five destinations on Guanabara Bay, with passenger capacities between 645 and 2,000. The system ranks fourth in the world in the number of commuters, transporting 20 million passengers annually. Like any other fossil-fuel based transport mode, the ferries emit pollutants that affect the air quality and climate in the vicinity of its operation area. Unfortunately, information on air pollutant concentrations on-board ferries and maritime terminals is scarce, which hinders the accurate assessment of personal exposure to air pollutants in these microenvironments. Thus, this pioneering research aimed to characterise the concentrations of fine particulate matter (with aerodynamic diameter smaller than 2.5 µm, PM2.5), black carbon (BC), particle number (PN) and total volatile organic compounds (TVOC) during five days on-board ferries connecting the cities of Rio de Janeiro and Niterói. The study used portable instruments operated continuously at high temporal resolution to capture the fine spatiotemporal features during the different phases of the commutes. In addition, PM2.5 and BC concentrations were collected at the kerbside in front of Niterói and Rio de Janeiro ferry terminals. The results from the fixed monitoring showed mean BC and PM2.5 concentrations of 4.5 ± 7.5 µg m-3 and 13.5 ± 13.6 µg m-3 in Niterói, and 4.6 ± 9.3 µg m-3 and 10.6 ± 7.7 µg m-3 in Rio de Janeiro, respectively. Mean BC and PM2.5 concentrations on-board the ferries were up to three- and six-fold higher than the kerbside concentrations, respectively, whilst PN and TVOC concentrations were comparable between these two microenvironments. The air pollutant concentrations were highly heterogeneous on-board the ferries, with the lower deck (LD) being more polluted than the upper deck (UD) in terms of BC (15.7 ± 36.8 µg m-3 vs. 9.3 ± 21.5 µg m-3) and PM2.5 (66.9 ± 65.4 µg m-3 vs. 39.4 ± 36.8 µg m-3 ). On the other hand, mean PN concentrations were slightly higher in the UD, with a large variability (30,010 ± 34,582 # cm-3 vs. 26,655 ± 36,508 # cm-3). The mean TVOC concentration in the UD was 1,537± 5,276 ppb, but a comparison between decks was not possible due to the availability of only one monitor. Infiltration of smoke plumes through the windows in the oldest ferries increased the mean BC, PN and PM2.5 concentrations by 2, 5 and 21 folds compared with the newest ones that operated with air conditioning systems (A/C) and closed windows. Conversely, TVOC concentrations were 150-fold higher in the newest ferries, which is hypothesised to come from formaldehyde and other VOC from decorating materials and furniture. Mean noA/C:A/C ratios were 3.5, 2.7 and 2.5, for BC, PM2.5 and PN, respectively. The most pollutated phase of the commute was manoeuvring for docking and undocking, when the engines operated at higher load to adjust the ferry position. In closing, this study showed that despite the advantages of a maritime mass transport system, commuters and (potentially, crew members) are exposed to disproportionately high concentrations of some SLCP during the commutes which, in the long term, may affect their health.